Study of Kidney Repair Mechanism of Cassava Leaf Extract on Gentamicin induced Nephrotoxicity - Rena Normasari; Rosita Dewi; Sheilla Rachmania (Faculty of Medicine, University of Jember, 2017)
Drugs consumption like gentamicin caused damage and decreased of kidney function. Cassava leaf contain lots of micronutrients, such as vitamin C, vitamin A and carotenoids, which also as an antioxidant. The results of the study conducted by Almashuri proved that cassava leaf have high levels of carotenoid compounds. The purpose of this study was to determine the effect of cassava leaf extract on the repairment of renal damage in mice in vivo. This research is true experimental using mice (mus musculus) and were grouped into 5 groups. Two control groups (positive and negative) and 3 treatment groups (cassava leaves 150, 300, and 450 mg / day). Gentamicin is given every day for 14 days and then observed on serum levels of creatinine along with histopathological scores of kidneys’ damage. Statistical analysis showed a significant reduction in serum levels of creatinine (P <0.05) and a significant decrease in renal histopathologic score. This study suggests that cassava leaf extract can repair kidney damage as a result gentamicin-induced nephrotoxicity in mice.Keywords: cassava leaf extract, creatinin, kidney histopathology